Digital Devices on Learning Management System and its Consequences on Physical and Mental Health among University Students in Nepal - Joshi, Dirgha Raj; Neupane, Umesh; Sharma, Krishna Prasad; Joshi, Basnet Raj; Joshi, Pushpa Raj (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Digital tools and devices are being integrated in almost areas of human activities demanding the implementation of digital literacy in modern education, health, business, and other related activities. This study was one of few to investigate the competence of learning management system by use of digital resources, and their impact on physical and mental health in Nepalese university students. Material and methods: The cross-sectional online survey was conducted among the 300 MPhil scholars during the period of Jan. 2019 to Jul. 2019 through Google Form. The nature of information was in the form of qualitative and quantitative both because the tool contained open and closed questionnaire. Frequency, percentage, word cloud, bar chart, pi-chart and chi-square test were calculated at 95% confidence level. Results: Around two-third (61.7%) of the participants have had habits to use digital resources by sitting on chairs/tools. More than half (53.33%) reported that use of digital device has negative effect on physical health whereas only 12% reported towards positive effect and 8.33% were not care on the effect of using digital devices on physical health. In case of mental health, around half (46.0%) have positive effect on mental health even around one-fourth (24%) have found to be negative effect however 3.3% did not care about the effect of using digital devices. The technology users with the distance greater than 3 ft. have less problems as compared to others. An insignificant association is observed in the effect on physical and mental health with respect to gender, age, years of using mobile and laptop except as the case of distance of digital devices with effect on mental health. Conclusion: The use of digital resources has negative effect on physical health and positive effect on mental health. Use of such resources with the distance greater than 3 ft. is better for health however the limited use of digital tools, use as per need only, use by making schedule, mediation, to take suggestion by the doctors, use without monotonous, appropriate breaks and comfortable body posture are major are the major techniques for the safe use of digital resources.